A study to develop a self instructional module (SIM) based on the learning needs of the Anganwadi workers regarding malnutrition among the children below six years of age, in urban ICDS centers Agra (Uttar Pradesh) - Maneesh Kumar, Mr. (International Journal of Nursing Research, 2023)
Aim: The objective is 1. To assess the learning needs of AWWs regarding malnutrition. 2. To develop a selfinstructional module based on learning needs. 3. To evaluate the effectiveness of the module. Method: Fifty AWWs from urban ICDS centers of Agra were included as samples by purposive sampling. Data to assess the knowledge was collected by close-ended questionnaire with 50 items with maximum score of 50. The felt learning needs were assessed by open-ended questionnaire. Reliability of the questionnaire was tested by test-retest method and the tool was found to be reliable (r = 0.83). Validity was tested by consultation with guides and experts from the related field. Results: Area wise mean percentage was highest (68.0%) in the area 'assessment of malnutrition', it was higher (57.0%) in the area prevention of malnutrition, 41.0 in the area 'management of malnutrition' and 40.0 for the area 'factors related to malnutrition'. Total mean percentage of knowledge scores of AWWs improved from 53.2% to 97.6%. Further, area wise knowledge mean percentage improved from 40.0% in pre-test to 94.0% in post-test in the area factors related to malnutrition'. The same increased from 57.0% to 97.3% for the area prevention of malnutrition. The mean percentage for the area 'management of malnutrition' was 41.0% in pre-test which increased to 99.0% in post-test and means the percentage of the area 'assessment of malnutrition' was 68.0% in pre-test whereas it was 100.0% in post-test. Further chi-square test indicated no association between the post-test knowledge scores and demographic variables of AWWs such as age, education, refresher course attended on malnutrition among children below six years of age and number of years back refresher course attended. Conclusion: There was a significant association between the years of experience as an Anganwadi worker and post-test knowledge scores of AWWs.